ANALISIS PENGARUH SOCIAL MEDIA MARKETING TERHADAP BRAND AWARENESS YANG BERDAMPAK TERHADAP PEMBENTUKAN BRAND IMAGE - Nurul Wahdini (Equilibrium Point : Jurnal Manajemen dan Bisnis, 2019)
Social media is a group of internet-based applications built on the ideological and technological framework of Web 2.0, and enables the creation and exchange of information content from internet users. Web 2.0 is the basis for the formation of social media. ) to Brand Awareness (X2) and Brand Image (Y) to PT XL Axiata.The sampling technique used in this study the author uses descriptive methods using survey techniques where each member of the population has the same opportunity to be chosen as a sample as a whole, the sample in this study were 124 samples. The results of the analysis show that there is a significant and positive influence between social media and brand awareness and the brand image of PT XL Axiata. This is possible because consumers of telecommunications operators who currently tend to do a lot of activities and find information about products from social media due to easy ways so that consumers feel the great benefits that can be obtained by using social media.